Students’ writing strategies in accomplishing final exams: lessons learned from an Islamic higher education institution - Siti Aisyah Pranita; Muhammad Husin Al Fatah (English Language Education Study Program, Faculty of Education and Teacher Training, Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, Indonesia, 2022)
This present study aims to describe tertiary students’ writing strategies and their response in accomplishing final exam. Grounded in a qualitative approach by using case study as the research design, 27 undergraduate students of an Islamic higher education institution volunteered to participate. Data were collected through semi-structured interview and documentation. The data were analyzed by reducing and transforming the data, then drawing conclusion. The study findings showed that the undergraduate students employed two types of writing strategies, i.e., free writing and brainstorming. There were 20 students using free writing strategy, and seven of them using brainstorming strategy. Most of them shared their positive responses in using the writing strategies, such as the feeling of happy and comfortable in accomplishing final exam. They narrated that using free writing strategy was very helpful to write an article journal better and more structured. On the contrary, there were also some EFL students who showed negative responses, e.g., the feeling of dizzy, lazy, and difficult to draft their ideas. This study recommends some empirical insights on how university teachers and faculty members manage final exams to accelerate students’ writing strategies.